γ-Aminobutyric AcidB(GABAB)-Receptor Mediation of Different In Vivo Effects of γ-Butyrolactone - Mauro A.M. Carai; Carla Lobina; Paola Maccioni; Claudia Cabras; Giancarlo Colombo; Gian Luigi Gessa (Elsevier, 2008)
The endogenous brain constituent, γ-hydroxybutyric acid (GHB), as well as its prodrug, γ-butyrolactone (GBL), have recently gained interest in the drug addiction field due to their abuse potential and fatalities caused by overdose. It is known that GHB has two sites of actions: the γ-aminobutyric acidB(GABAB) receptor and a specific-GHB binding site. The present study was designed to extend to GBL the investigations on the contribution of the GABABreceptor and the specific-GHB binding site to its in vivo effects. To this aim, DBA mice were pretreated either with GABAB-receptor antagonists, (3-aminopropyl)(diethoxymethyl)phosphinic acid (CGP 35348) and (2S)(+)-5,5-dimethyl-2-morpholineacetic acid (SCH 50911), or a putative antagonist of the specific-GHB binding site, 6,7,8,9-tetrahydro-5-hydroxy-5H-benzocyclohept-6-ylideneacetic acid (NCS-382), prior to the administration of doses of GBL that induced hypothermia, motor-incoordination (measured as motor-impairment at the Rota-Rod task), and sedation/hypnosis. The capability of SCH 50911 and NCS-382 to protect against GBL-induced lethality was also investigated. Pretreatment with either GABAB-receptor antagonist completely prevented GBL-induced hypothermia, motor-incoordination, and sedation /hypnosis. SCH 50911 also provided complete protection against GBL-associated lethality. Vice versa, NCS-382 failed to exert any antagonistic or protective effect. These results suggest that the in vivo GBL effects tested in the present study are mediated by activation of the GABABreceptor. Keywords:: γ-butyrolactone (GBL), γ-hydroxybutyric acid (GHB), γ-aminobutyric acidB(GABAB)-receptor antagonist (CGP 35348, SCH 50911), antagonist of the specific-GHB binding site, NCS-382